Prática do Desmame da Ventilação Mecânica e Extubação nas Unidades de Terapia Intensiva Pediátricas e Neonatais do Brasil - Bacci, Suzi Laine Longo dos Santos (2017)
Purpose: Weaning from mechanical ventilation (MV) is a complex process that involves clinical aspects, contextual aspects, and the characteristics of health professionals who work in an intensive care service. Regarding the clinical aspects, previous studies have shown great variability of protocols, strategies and criteria used in the process of weaning from MV and extubation in neonatal and pediatric intensive care patients. Furthermore, the management of this process can be influenced by contextual aspects of the intensive care units (ICUs) structure and organization, and professional aspects of the team involved in this scenario. The aim of this study was to describe clinical aspects of the weaning practices in neonatal, pediatric, and mixed (neonatal and pediatric) ICUs in Brazil, as well as the organizational aspects associated with the physiotherapist's performance to conduct this process. Methods: A cross-sectional survey was carried out by sending an electronic questionnaire to 298 neonatal, pediatric, and mixed ICUs in Brazil (January to November 2016). Data on weaning practices and extubation were collected. Only one representative of each unit answered to the questionnaire. Results: This study assessed questionnaires from 146 ICUs (49.3% neonatal, 35.6% pediatric and 15.1% mixed). 57.5% of the ICUs surveyed apply weaning protocols. In neonatal and mixed ICUs using weaning protocols the standardized gradual reduction of ventilator support was the most used method of liberation from MV (60.5% and 50.0%, respectively). In pediatric ICUs using weaning protocols the spontaneous breathing trial (SBT) was the most common (53%). During SBT the most common ventilation mode in all ICUs was PSV+PEEP with PSV=10.03 ± 3.15 cmH2O and the trial lasted from 35.76 ± 29.03 minutes in neonatal ICUS to 76.42 ± 41.09 minutes in pediatric ICUs. The SBT parameters, weaning modes, and time considered for extubation failure varied regardless of ICU age profile. Clinical evaluation and arterial blood gas are frequently criteria used to assess readiness for extubation, regardless of ICU age profile. Regarding the professionals involved in the process of weaning and extubation, the physical therapist frequently conducted this process (66.7%). However, the professional responsible for conducting weaning and extubation decision varied regardless of ICU age profile. The three ICUs age profile frequently had an exclusive physical therapist. However, physiotherapeutic care 24 hour/7 days per week was predominant in pediatric ICUs (56.0%). Moreover, when the physical therapist was 24 hours/7 days per week, he was responsible for the extubation decision and the patients were successfully extubated on the first try. Conclusion: In Brazil, the clinical practice towards weaning from MV and extubation occur according to the ICU age profile. The ICUs with physical therapy assistance 24 hours/7 days per week were more associated with the use of weaning protocol, extubation decision and success of the first attempt of extubation.